Junk Food Consumption Pattern among Undergraduate Students in Urban Regions of Nepal - Chuwan, Nar Kumar (BARUN Journal, 2025)
Junk food consumption is a serious problem among the urban youth. Various researches show that it is bad for health from both public health and food security and nutrition perspectives. This study examined the junk food consumption patterns among undergraduate students in Kathmandu, Nepal. It aimed to explore the preferences, consumption frequency, and the socio-demographic factors shaping the junk food consumption pattern. Theory of planned behaviors (TPB) was employed to analyze the junk food consumption pattern by hypothesizing that individual behavior is influenced by attitudes, subjective norms, and perceived behavioral control. A cross-sectional survey was conducted in two purposively selected private colleges of Kathmandu. Two hundred and five students were chosen as sample using stratified random sampling to ensure proportional representation by college and faculty. The results of ordinal logistic regression showed that the goodness-of-fit suggested a reasonable model fit (Deviance χ² (563) = 408.309, p = 1.000). The dependent variable was junk food consumption frequency. Statistically significant predictors of higher consumption frequency were religion (Hinduism and Buddhism, p < .05) and convenience factors (easy availability, p = .006; instant consumption, p = .004), while variables such as sex, age, and faculty were not statistically significant. The study found that religion and convenience-based influences increase junk food consumption more than demographic factors which supports the TPB. The study offers valuable insights for policymakers, community leaders, and other stakeholders involved in food security initiatives, emphasizing a holistic approach to regulating junk food availability and promoting healthier diets.